Educators' self-reported training, use, and perceived effectiveness of evidence-based classroom management practices. Issue 1 (2nd January 2018) - Cooper, Justin T.; Gage, Nicholas A.; Alter, Peter J.; LaPolla, Stefanie; MacSuga-Gage, Ashley S.; Scott, Terrance M.
ABSTRACT: A survey study of 248 educators in four states was conducted to identify respondents' formal training, use, and perceived effectiveness of 37 evidence-based classroom management practices within four general categories: (a) antecedent-based, (b) instructionally based, (c) consequence-based, and (d) self-management. Results indicated that, on average, only one in three respondents received formal training in most of the practices. However, 91% of responding educators reported formal training with antecedent-based practices, while just over half received formal training in self-management strategies. Results also indicated that formal training significantly predicted use of practices, but not perceptions of effectiveness. We describe implications for improving preservice and in-service teachers' formal training on evidence-based classroom management practices, as well as implications for practicing teachers.